Effects of Chronic Exercise on Endothelial Progenitor Cells and Microparticles in Professional Runners - Bittencourt,Célia Regina de Oliveira (2017)
Abstract Background: The effects of chronic exposure to exercise training on vascular biomarkers have been poorly explored. Objective: Our study aimed to compare the amounts of endothelial progenitor cells (EPCs), and endothelial (EMP) and platelet (PMP) microparticles between professional runners and healthy controls. Methods: Twenty-five half-marathon runners and 24 age- and gender-matched healthy controls were included in the study. EPCs (CD34+/KDR+, CD133+/KDR+, and CD34+/CD133+), EMP (CD51+) and PMP (CD42+/CD31+) were quantified by flow-cytometry. All blood samples were obtained after 12 h of fasting and the athletes were encouraged to perform their routine exercises on the day before. Results: As compared with controls, the CD34+/KDR+ EPCs (p=0.038) and CD133+/KDR+ EPCs (p=0.018) were increased, whereas CD34+/CD133+ EPCs were not different (p=0.51) in athletes. In addition, there was no difference in MPs levels between the groups. Conclusion: Chronic exposure to exercise in professional runners was associated with higher percentage of EPCs. Taking into account the similar number of MPs in athletes and controls, the study suggests a favorable effect of exercise on these vascular biomarkers.